An 11‐channel radio frequency phased array coil for magnetic resonance guided high‐intensity focused ultrasound of the breast. Issue 1 (16th March 2012) - Minalga, E.; Payne, A.; Merrill, R.; Todd, N.; Vijayakumar, S.; Kholmovski, E.; Parker, D. L.; Hadley, J. R.
Abstract In this study, a radio frequency phased array coil was built to image the breast in conjunction with a magnetic resonance guided high‐intensity focused ultrasound (MRgHIFU) device designed specifically to treat the breast in a treatment cylinder with reduced water volume. The MRgHIFU breast coil was comprised of a 10‐channel phased array coil placed around an MRgHIFU treatment cylinder where nearest‐neighbor decoupling was achieved with capacitive decoupling in a shared leg. In addition a single loop coil was placed at the chest wall making a total of 11 channels. The radio frequency coil array design presented in this work was chosen based on ease of implementation, increased visualization into the treatment cylinder, image reconstruction speed, temporal resolution, and resulting signal‐to‐noise ratio profiles. This work presents a dedicated 11‐channel coil for imaging of the breast tissue in the MRgHIFU setup without obstruction of the ultrasound beam and, specifically, compares its performance in signal‐to‐noise, overall imaging time, and temperature measurement accuracy to that of the standard single chest‐loop coil typically used in breast MRgHIFU. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.